Implementation of Security in RFID Tag Data Transmissions with DES Cryptography - ahmad fali oklilas; ahmad heryanto; anggoro prasetyo (Annual Research Seminar (ARS), 2017)
One use of RFID is used as a user authentication tool that can provide more access to a system. Security is much needed on RFID. If authentication rights are misused for the wrong thing then it is very dangerous. The scheme used is to send RFID Tag ID data as a unique authentication code. RFID Tag ID will be sent from client to server using local network scale. RFID Tag ID data transmission can be done using wireless transmission media. When shipping the "bugs" can steal data with sniffing techniques. To minimize the risk of data theft can be applied data encryption method with DES algorithm. There will be a modified 8-bit RFID Tag ID which will add 8-bit user passwords. So 16 bit data can be processed with DES algorithm. With the data encryption at the time of delivery from client to server then data sent will be encrypted. So tappers can not misuse existing data.